Upaya Peningkatan Penerimaan dan Kemampuan Ibu dalam Menstimulasi Bayi Melalui Terapi Kelompok Terapeutik Bayi Peka Budaya: Studi Kasus - Budiarto, Eka; Kusuma, Nur Intan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Mental nursing services are not limited to the patients with mental disorders and psychosocial problems, but the healthy peoples are included the patients. The method of service to healthy patients by giving the stimulation according to the range of age development. One of them is the age of the baby. Stimulation in infants aims to optimize the achievement of the task of developing trust. Stimulation in infants can be given in the form of group therapy, namely infants therapy of therapeutic group. Therapy of therapeutic group for infants is proven to increase parental knowledge and psychosocial development of infants. However, the care that given to a baby boy (13 month old ) shows that the family still adhere to a cultures that do not support the implementation of therapy of therapeutic group. Busyness helps husbands work, individualistic culture and the perception of socialization in groups are just a waste of time and not useful, and the culture of utilization of health services is less a challenge for nurses in providing infants therapy of therapeutic group. Based on these conditions, infants therapy of therapeutic group is given by cultural approach. Infants therapy of therapeutic group is carried out by integrating cultural values with cultural identification, negotiation, and strengthening of good culture. The results obtained were infants therapy of therapeutic group with culturally considerate to infant increased maternal acceptance of therapeutic group therapy and mothers felt increasing in cognitive and psychomotor abilities in stimulating infants growth and development in order to achieve the task of developing infants trust.